Transformasi Otoritas Keagamaan di Era Digital: Analisis “Medium is the Message” pada Konten Youtube Shorts - Asep Iwan Setiawan; Hikmatussahri Ramadan; Muhammad Fahmi Syihab (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The rapid development of digital media has fundamentally transformed the landscape of religious communication, particularly in Muslim-majority societies. The emergence of short-form video platforms such as YouTube Shorts has raised critical questions about how religious messages are constructed, distributed, and received in algorithmically-driven digital environments, and how traditional religious authority is renegotiated in the process. This study aims to analyze the transformation of religious messages and authority in YouTube Shorts-based da’wah content as part of the broader phenomenon of digital religious communication. This research employs a qualitative approach with a case study design to explore in depth the discursive practices and meaning construction within digital spaces. Data were collected through non-participant observation of YouTube Shorts content, semi-structured interviews with digital da’wah creators and audiences, and documentation including content metadata and user interactions. Informants were selected using purposive and snowball sampling techniques based on relevance and level of engagement in producing or consuming religious content. The findings reveal four main themes: (1) simplification and fragmentation of religious messages due to time constraints, (2) the dominance of algorithms in shaping content visibility and structure, (3) the shift of religious authority from knowledge-based legitimacy to digital popularity, and (4) audience interactivity in constructing collective meaning through comment sections. These findings indicate that digital media not only functions as a medium of dissemination but also actively shapes how religious messages are produced, distributed, and interpreted. In conclusion, this study highlights that the transformation of religious communication in the digital era contributes theoretically to strengthening the concepts of digital religion and mediatization, while offering practical implications for adaptive yet substantive da’wah strategies. The study also recommends enhancing digital religious literacy and conducting further cross-platform research to deepen understanding of religious dynamics in the new media era.